Involvement of glutathione availability on arsenic tolerance in Pistia stratiotes L. (ARACEAE) - Silva, Vinícius Melo da (2021)
Glutathione is a multifunctional peptide important for response to multiple stress conditions in plants, such as arsenic (As) stress. Following recent results, which demonstrate that aquatic macrophytes, such as Pistia stratiotes, exhibit As tolerance linked to a glutathione metabolism, we investigated in presented study, how much glutathione availability can alter plant response to As, using a tolerant As concentration determined in the literature for P. stratiotes, but under glutathione limitation, with a glutathione synthesis inhibitor, DL-Buthionine sulfoximine (BSO). The plants were grown in the nutrient solution, pH 6.5, 1/2 ionic strength, and used in two experimental approaches. The first approach aimed to identify the most critical demands in glutathione metabolism during As exposure. The experiment consisted of a factorial design with 2 concentrations of sodium arsenite (0 and 5 µM) and 5 BSO concentrations (0, 25, 50 100, and 200 µM) in 5 replications and one plant per pot (0.25 L) exposed for 48 hours in a controlled condition in a growth room. The second approach aimed to evaluate how glutathione availability can alter As concentration in plant and physiological processes, such as photosynthesis, respiration, sugar content and antioxidant parameters. The experiment consisted of 4 treatments: Control (nutritive solution), BSO (200 µM), sodium arsenite (5 µM) and As (5 µM) + BSO (200 µM), in 5 replications and one plant per pot (0.25 L) exposed for 48 hours in a controlled condition. In both experiments, As concentration in roots decreased about 50% under BSO treatments, with increased As translocation to leaves at 3-times. Arsenic exposure induced glutathione metabolism responses, especially in roots, with increased activity of antioxidant enzymes and enzymes and compounds linked to As detoxification. All glutathione metabolism was affected by BSO, starting from γ-glutamyl-cysteine synthetase (γ- ECS), followed by depletion of glutathione content in plant. In our experiments, Glutathione peroxidase (GPX) and Dehydroascorbate reductase (DHAR) indicated high sensitivity to glutathione availability than Glutathione-S transferase (GST) and the Phytochelatins (PC) content. However, glutathione reductase functions are well preserved in glutathione depletion; furthermore, GSH-independent functions, such as Catalase (CAT), Ascorbate Peroxidase (APX) and Ascorbate increasing their activity. Other aspects were also affected by glutathione, especially in photosynthesis, with decreased carbon assimilation rates linked to increased oxidative stress markers and changes in starch content in plant. Also was affected by As exposure the pigment content, heat dissipation and electron transport rate. Furthermore, this damage is enhanced by glutathione depletion in two respects, the first linked to increased As translocation to leaves and the second to decreased redox protection on BSO exposure. Based on the results, it is possible to conclude that the tolerance of P. stratiotes to As can be largely explained by the activity of glutathione metabolism, which participates in different aspects of the plant's survival in environments contaminated with arsenic and can define the performance of this aquatic plant in phytoremediation processes of this contaminant. Keywords: GSH. Arsenite. BSO. Aquatic Plant. Phytoremediation.